Hot topics in the mechanisms of pulmonary arterial hypertension disease: cancer-like pathobiology, the role of the adventitia, systemic involvement, and right ventricular failure. (November 2019) - Spiekerkoetter, Edda; Goncharova, Elena A.; Guignabert, Christophe; Stenmark, Kurt; Kwapiszewska, Grazyna; Rabinovitch, Marlene; Voelkel, Norbert; Bogaard, Harm J.; Graham, Brian; Pullamsetti, Soni S.; Kuebler, Wolfgang M.
In order to intervene appropriately and develop disease-modifying therapeutics for pulmonary arterial hypertension, it is crucial to understand the mechanisms of disease pathogenesis and progression. We herein discuss four topics of disease mechanisms that are currently highly debated, yet still unsolved, in the field of pulmonary arterial hypertension. Is pulmonary arterial hypertension a cancer-like disease? Does the adventitia play an important role in the initiation of pulmonary vascular remodeling? Is pulmonary arterial hypertension a systemic disease? Does capillary loss drive right ventricular failure? While pulmonary arterial hypertension does not replicate all features of cancer, anti-proliferative cancer therapeutics might still be beneficial in pulmonary arterial hypertension if monitored for safety and tolerability. It was recognized that the adventitia as a cell-rich compartment is important in the disease pathogenesis of pulmonary arterial hypertension and should be a therapeutic target, albeit the data are inconclusive as to whether the adventitia is involved in the initiation of neointima formation. There was agreement that systemic diseases can lead to pulmonary arterial hypertension and that pulmonary arterial hypertension can have systemic effects related to the advanced lung pathology, yet there was less agreement on whether idiopathic pulmonary arterial hypertension is a systemic disease per se. Despite acknowledging the limitations of exactly assessing vascular density in the right ventricle, it was recognized that the failing right ventricle may show inadequate vascular adaptation resulting in inadequate delivery of oxygen and other metabolites. Although the debate was not meant to result in a definite resolution of the specific arguments, it sparked ideas about how we might resolve the discrepancies by improving our disease modeling (rodent models, large-animal studies, studies of human cells, tissues, and organs) as well as standardization of the models. Novel experimental approaches, such as lineage tracing and better three-dimensional imaging of experimental as well as human lung and heart tissues, might unravel how different cells contribute to the disease pathology.